1979
DOI: 10.1002/ange.19790911233
|View full text |Cite
|
Sign up to set email alerts
|

1, 4‐Dihydro‐1, 4‐diazocin und N, N′‐Disubstitutionsprodukte ‐ eine rationelle Synthese

Abstract: Bausteine (x = 2, 3) unter Berucksichtigung der Metall -Metall-Bindungen betrachtet: Wahrend Nb(3) eine 1 8-Elektronenkonfiguration besitzt und somit keines weiteren Koordinationspartners bedarf, sind die beiden (q5-CsH5)Nb(C0),-Fragmente [Nb(l) bzw. Nb(2)] als 16-Elektronen-Spezies koordinativ ungesattigt. Hier bietet sich nun die sterisch verfugbare Nb(3) CO-Gruppe an und verhilft als zweifache Donor-Briicke diesen Elektronenmangelzentren zur Absattigung. In dieser Funktion sehen wir die molekulare Ursache d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…14 128.291, and 15 128,301 and the ring C atoms bound to the N atoms in 13[26]. 14 128.291, and 15 128,301 and the ring C atoms bound to the N atoms in 13[26].…”
mentioning
confidence: 99%
“…14 128.291, and 15 128,301 and the ring C atoms bound to the N atoms in 13[26]. 14 128.291, and 15 128,301 and the ring C atoms bound to the N atoms in 13[26].…”
mentioning
confidence: 99%
“…The extraordinary conformational variability of 1,4-dihydropyrazines as exemplified by the few structurally characterized derivatives [88,120,121] is also reflected by their spectroscopy. IH-NMR studies have suggested that there might be a weak paramaguetic ring current operating in compound 3 as compared to the non-conjugated tetrahydro derivative 9 [78,89] and in contrast to the "aromatic" 107r electron analogue 10 [181].…”
Section: K"'-'n~mentioning
confidence: 99%